The importance of participation and corresponsibility in the management of solid urban waste - Del Carmen Niño, Viridiana; Rodríguez Herrera, América L.; Juárez López, Ana Laura; Sampedro-Rosas, Maria Laura; Reyes-Umaña, Maximino; Silva-Gómez, Sonia E. (Acta Universitaria, 2019)
The management of urban solid waste (MUSW) in Xaltianguis is done by the community, generating pollution and environmental degradation. This article studies the MUSW focusing on community participation. To estimate the generation, composition and emission, the climate calculator was applied. The MUSW diagnosis was obtained by applying a survey and making interviews. The open dumpsites (OD) were georeferenced using geographic information systems. The results showed a generation of 1017 t/a of waste; 62.1% were organic and emitted 1036 t/a of CO2-eq. There were two collection systems, the municipal operated weekly, while the informal daily deposited in OD. Other 22 OD were registered. 48% of the population considers participating. Practices such as reusing (44%) and recycling (2.3%) would contribute to an efficient MRSU, but this can only be achieved with co-responsibility and commitment of the community and the municipality.